Efetividade de um programa de exercícios no condicionamento físico, perfil metabólico e pressão arterial de pacientes hipertensos - Monteiro, Henrique Luiz [UNESP]; Rolim, Lívia M. C. [UNESP]; Squinca, Daniela A. [UNESP]; Silva, Fernando C. [UNESP]; Ticianeli, Carla C. C.; Amaral, Sandra Lia do [UNESP] (FapUNIFESP (SciELO), 2007)
Background and objective: It has been shown that aerobic exercise is useful to reduce arterial pressure, however, the effectiveness of an exercise program is still controversial and not very well analyzed among populations with low-income. The objective of the present study was to set up an individualized physical fitness program - Projeto Hipertensão - focused on hypertensive people, patients from a Health Basic Unit (HBU) and, after that, to investigate the effects of this program on physical fitness, metabolic profile and pressure levels. Methods: Sixteen hypertensive women (56 ± 3yrs) under regular pharmacological treatment underwent 4 months of a supervised aerobic and stretching exercise program (3 sessions/wk, 90 min/session, 60% of V̇O 2 max). Several physical and metabolic variables were compared before and after 4 months of training. Results: Training significantly reduced systolic arterial pressure (SAP, -6%), improved cardio-respiratory fitness (+42% of V̇O2max), flexibility (+11%) and plasma glucose content (-4%). BMI and % fat did not change. Besides modifying metabolic profile, it was found that training presented significant correlations between individual initial values of cholesterol total level (CT), high density lipoprotein (HDL-C) and low density lipoprotein (LDL-C) and its responses after exercise. Conclusions: The study shows that exercise programs can be personalized for hypertensive patients from a HBU and confirms the effectiveness of exercise on AP, physical fitness, flexibility and lipid profile on hypertensive patients. The expressive reduction of AP in hypertensive subjects suggests that this exercise intervention should be emphasized on other health centers which assist low-income population.
Exercise program effectiveness on physical fitness, metabolic profile and blood pressure of hypertensive patients
Keywords: Arterial pressure; Exercise training; Lipid profile